2012
DOI: 10.1007/s11469-012-9398-x
|View full text |Cite
|
Sign up to set email alerts
|

Genderedness of Bar Drinking Culture and Alcohol-Related Harms: A Multi-Country Study

Abstract: This study explores whether associations between consuming alcohol in bars and alcohol-related harms are consistent across countries and whether country-level characteristics modify associations. We hypothesized that genderedness of bar drinking modifies associations, such that odds of harms associated with bar drinking increase more rapidly in predominantly male bar-drinking countries. Multilevel analysis was used to analyze survey data from 21 countries representing five continents from Gender, Alcohol, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Although the differences are not always significant, in all 10 societies such harms were more often reported by men than by women. This may partly reflect widely followed conventions concerning the gendering of drinking‐related sociability with previously unknown people, for instance in taverns ; however, the results are not very different when the respondent's own drinking, presumably related to such conventions, is taken into account. Further studies could examine the contribution of exposure to high‐risk venues to harms from strangers, as prior work in some countries suggests that frequent drinking in bars or at parties increases the risk of violent interactions with other drinkers (e.g.…”
Section: Discussionmentioning
confidence: 81%
“…Although the differences are not always significant, in all 10 societies such harms were more often reported by men than by women. This may partly reflect widely followed conventions concerning the gendering of drinking‐related sociability with previously unknown people, for instance in taverns ; however, the results are not very different when the respondent's own drinking, presumably related to such conventions, is taken into account. Further studies could examine the contribution of exposure to high‐risk venues to harms from strangers, as prior work in some countries suggests that frequent drinking in bars or at parties increases the risk of violent interactions with other drinkers (e.g.…”
Section: Discussionmentioning
confidence: 81%
“…The narration of particularly raucous drinking sessions or ‘drinking tales’ [ 68 ] reflected a nostalgia for youth, Soviet era workplace bonds [ 21 ] and an assertion of masculinity. The all-male context of heavy drinking contrasts with Western European countries where drinking is more likely to take place in more gender-neutral contexts such as restaurants and the home [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research utilizing the 1984, 1995, and 2005 U.S. National Alcohol Surveys to examine drinking context and alcohol problems among Black, Hispanic and White men and women and found that those who drank mostly at bars and other public venues were at a higher risk of arguments, fights, and drunk driving than those who drank less in these settings (Nyaronga et al, 2009). In a multi-national study, individual-level bar drinking frequency was associated with past year harms from someone else’s drinking (Roberts et al, 2013). Event-based analysis of bar-going adult women has documented that sexual victimization often occurred physically outside of bars, with perpetrators who were intoxicated (Parks, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Event-based analysis of bar-going adult women has documented that sexual victimization often occurred physically outside of bars, with perpetrators who were intoxicated (Parks, 2000). Notably, country-level genderedness of bar drinking (the proportion days of drinking in bars in a country in the past year by men) modified the associations between bar going and assault, family problems, and work harm, with the likelihood of harms associated with bar drinking increasing at a slower rate in countries with predominately male bar drinking (Roberts et al, 2013). Relatedly, studies have demonstrated that women experience violent and sexual victimization in bar settings (Parks, 2000).…”
Section: Introductionmentioning
confidence: 99%